Prophecy in Literature - Suria Dewi Fatma; Silvia Rosa; Zurmailis Zurmailis (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2020)
This study discusses how a phenomenon can affect civilization and the outlook on society. Prediction is so important to uncover major events that have occurred at a certain period or period. Forecast defined as attempts to acquire knowledge through occult ways or using certain rituals.   Said forecaster derived from Arabic which means a science Raml for interpreting, judging, see and predict the fate of someone in the future. Activities divination fortune-telling in the novel Sabdo Palon Pudarnya Surya Majapahit by Dhamar Shashangka refers to signs/phenomena that come from nature itself, namely with the emergence of a red lunar eclipse (blood moon) lunar eclipse, Chandra Kartika, earthquake, and head of the earth at Majapahit sky. The conclusions from this study indicate that predictions are so important to answer someone's curiosity and curiosity about things that are beyond the limits of ordinary human abilities and to reveal it all also requires help from someone who has extraordinary abilities and knowledge of the prophecy itself. In this novel, the translator is focused on the figure of Sabdo Palon